2015
DOI: 10.14414/jebav.v18i3.513
|View full text |Cite
|
Sign up to set email alerts
|

The comparative analysis of discretionary accruals viewed from the styles of audit and IFRS adoption

Abstract: Discretionary accruals in auditing have been the essential factor. Therefore, an analysis of this factor viewed from different styles of audit and IFRS adoption can be more interesting to study. This study discusses financial statement comparabil-ity in terms of audit style and IFRS adoption. It took the sample consisting of 43 manufacturing companies listed in Indonesia Stock Exchange; all have published their financial statements for the period of 2010-2013. The data were analyzed by using Kruskal-Wallis tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study still shows the variability results. Three of six studies indicate that there is no difference in earnings management before and after the adoption of IFRS (Dewi & Ahmar, 2015;Karyada & Irwanto, 2017;Kusumaningwedari & Oktorina, 2017) while three other studies found IFRS adoption had an effect on the level of earnings management (Hendika & Hudiwinarsih, 2014;Sulhani & Darisman, 2015;Widyawati & Anggraita, 2013). The difference in outcomes may be due to the research being undertaken in the early stages of the IFRS adoption so that there are still companies that have not implemented IFRS in their accounting policies.…”
Section: Methodsmentioning
confidence: 99%
“…The study still shows the variability results. Three of six studies indicate that there is no difference in earnings management before and after the adoption of IFRS (Dewi & Ahmar, 2015;Karyada & Irwanto, 2017;Kusumaningwedari & Oktorina, 2017) while three other studies found IFRS adoption had an effect on the level of earnings management (Hendika & Hudiwinarsih, 2014;Sulhani & Darisman, 2015;Widyawati & Anggraita, 2013). The difference in outcomes may be due to the research being undertaken in the early stages of the IFRS adoption so that there are still companies that have not implemented IFRS in their accounting policies.…”
Section: Methodsmentioning
confidence: 99%